ORDERING AND CLASSIFICATION OF THE SILESIAN VOIVODESHIP REGION WITH RESPECT TO A HEALTH CARE SYSTEM ACTIVITY - Nieszporska, Sylwia (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
The health care system in Poland or any other country should ensure an equal and unrestricted availability of the health service to its population. This idea, though being noble and harmonious with the country’s constitution, seems to differentiate small administrative regions of the Silesian voivodeship. Therefore the presented paper is an attempt to estimate and analyse conditions of the health care system activity in this region. Those regions were systematized based on a structure of health care system. Also, a homogeneous groups of regions were created. The analysis is based on the cluster analysis.